Dragon Fruit Classification using Convolutional Neural Network - Tan, Ying Zhi (IRC, 2020)
The dragon fruit ripeness classification is typically the process for identify and classify dragon fruit based on ripening stages. The main objective of this project is to develop a classification system of ripeness stages for dragon fruit. The project will make use of Deep Learning approach and algorithm with Python programming language for the ripeness classification.